Unravelling the nexus: a conceptual exploration of the interplay between self-congruity, satisfaction, and brand loyalty in urban coffee shops / Nur Adriana Yusli, Dr. Muhammad Safuan Abdul Latip and Dr. Ahmad Esa Abdul Rahman - Yusli, Nur Adriana; Abdul Latip, Muhammad Safuan; Abdul Rahman, Ahmad Esa (Universiti Teknologi MARA, Kedah, 2024)
The purpose of this conceptual paper is to investigate a potential study field concerning brand loyalty in coffee shops, as well as the mediating role self-congruity and overall satisfaction play in the relationship between the two. Recently, there has been a worldwide increase in the demand for coffee shops, and it is anticipated that this trend will continue to grow in the future. Consequently, customers’ brand loyalty has become more important for coffee businesses. However, there is a scarcity of research related to this specific area. The notion that customers who have a strong attachment to the coffee shop's brand are more likely to frequent the establishment again needs to be scientifically investigated. Thus, an in-depth literature review analysis was conducted within the realm of self-congruity and customer satisfaction in relation to brand loyalty in coffee shops. Future research directions and potential research framework are proposed for further exploration. The results have significant practical implications for coffee shop owners and marketers, who can utilise them to design effective branding and marketing strategies to enhance consumer loyalty in highly competitive urban marketplaces. This study contributes to the current literature on brand loyalty and its effect on the food and beverage sector, while also emphasising the need for more research in this field.